2020
DOI: 10.1097/gox.0000000000003080
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Cleft/Craniofacial Surgical Care after the COVID-19 Pandemic

Abstract: Background: It is anticipated that in due course the burden of emergency care due to COVID-19 infected patients will reduce sufficiently to permit elective surgical procedures to recommence. Prioritizing cleft/craniofacial surgery in the already overloaded medical system will then become an issue. The European Cleft Palate Craniofacial Association, together with the European Cleft and Craniofacial Initiative for Equality in Care, performed a brief survey to capture a current snapshot during a rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 3 publications
(2 reference statements)
0
18
0
Order By: Relevance
“… 16 Although “elective” 17 in nature, this definition during the current global pandemic requires further discussion as there is a relationship to the timing of cleft surgery and long-term treatment outcome. 18 , 19 Though it has been suggested that a short delay in the timing of primary cleft lip surgery 7 may be appropriate during a global pandemic our data shows that the effect of the COVID-19 pandemic on decreased surgical rates continues and may become an “intermediate term” rather than “acute” problem.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“… 16 Although “elective” 17 in nature, this definition during the current global pandemic requires further discussion as there is a relationship to the timing of cleft surgery and long-term treatment outcome. 18 , 19 Though it has been suggested that a short delay in the timing of primary cleft lip surgery 7 may be appropriate during a global pandemic our data shows that the effect of the COVID-19 pandemic on decreased surgical rates continues and may become an “intermediate term” rather than “acute” problem.…”
Section: Discussionmentioning
confidence: 78%
“…In a recent publication, a consensus of providers suggested that cleft lip surgery could be postponed for up to 3 months without adverse effects on the patient. 7 , 8 With the duration of the pandemic now well into 12+ months, deferred surgery may be falling outside this prescribed window. Effects on families have also been described in literature as decreasing confidence in hospitals to provide care and fear of the risk of contracting COVID-19 when seeking routine hospital care as altering health seeking behavior for surgery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Primary cleft lip repair was categorised as a medium priority as earlier lip repairs have been shown to benefit mother-infant interactions and bonding (Murray et al, 2007). Secondary speech surgery, symptomatic fistulae repair and secondary alveolar bone grafting were medium priorities due to their time-sensitive association with functional outcomes of speech and maxillary growth, although they occur at an older age and with a wider window of opportunity when compared to primary palatoplasty (Breugem et al, 2020). Secondary speech surgery and the repair of symptomatic fistulae may be warranted before the child enters primary education with an aim to achieve normal speech to help optimise educational performance (Sell et al, 2015).…”
Section: Prioritisation Of Surgical Proceduresmentioning
confidence: 99%
“…In a crowded healthcare system following delays to many areas of planned services, prioritisation of care will be vital. Breugem et al, (2020) conducted a survey of cleft priorities during COVID-19 with 218 cleft professionals in Europe, Asia and the USA. The respondents viewed airway intervention for Pierre Robin Sequence to be an emergency procedure.…”
Section: Interpretation and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation